Phenomenal Minimalist Ontology of the Self - Tourko, D. (Antinomii, 2021)
The article discusses the problem of whether the self, or the subject, is real. There are several realist and anti-realist solutions to this problem. The author interprets all possible positions concerning this issue as conceptions of a certain relationship between the phenomenal self (our experience of ourselves as subjects) and the ontological self (the referent of our self-representations as it exists apart from our self-experience). In line with what is called phenomenal, or experiential minimalism, the author concludes that the experiential dimension of the self is sufficient for it to be real without qualification. Providing an argument against anti-realism, the author differentiates between strong and reductive realism and maintain that selves criticized by anti-realists like Metzinger are things of strong realism (substantial and causally autonomous entities), while in fact selves might turn out to be the things of reductive realism (things emergent on other things). The author suggests a solution to another problem of the ontology of the self, namely the problem of characterization (What is the self, specifically?). By endorsing minimalism, the self is characterized as the experiential faculty. According to the suggested version of minimalism, having experience is a necessary and sufficient condition to be a self or a subject. All other properties ascribed to subjects in philosophical literature (such as self-awareness, moral agency, second-order desires or the ability to create autobiographical narratives) are contingent. Properties like these are of course attributes of subjects, but they are neither necessary nor sufficient for subjectivity. A subject who loses these properties does not cease to be a subject. On the contrary, a thing which has lost its experiential ability ceases to be a subject. In addition, there are non-human subjects who may lack all subjectivity-related features, except for the experiential faculty, and still be considered subjects. Phenomenal minimalism is a solution to the problem of the reality of selves. Subjects, or selves, are real as things with the experiential faculty. Finally, the author rejects pluralism (the idea that every subject is many things) and conventionalism (there is no non-contractual truth-apt proposition which serves as a solution to the characterization problem). Instead, essentialist realism is endorsed (the self, in a fundamental sense, is what is necessary for survival).